Information for contributors and readers - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The Military Technical Courier is indexed in DOAJ, ROAD and EBSCO Academic Search Complete databases; Supplement-section Military Economy Survey will be published in the Vojno delo